Angiographic Follow-Up of Traumatic Carotid Cavernous Fistulas Treated with Endovascular Stent Graft Placement - Archondakis, E. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Endovascular treatment (EVT) of carotid cavernous fistulas (CCFs) is based on various techniques, mainly those using detachable balloons. Coronary covered stent grafts have been sporadically used in the intracranial arteries and only 2 traumatic CCFs have been reported in the literature; moreover, there is poor information about the long-term follow-up. We present 8 cases of CCFs treated by the placement of a covered stent, 5 of which have a 1-year clinical and angiographic follow-up. METHODS: Eight patients with posttraumatic CCF were treated by positioning a covered stent in the intracranial internal carotid artery (ICA) to occlude the fistula. They received periodic clinical and angiographic follow-up to evaluate the patency and the stability of clinical results. RESULTS: In all cases, the symptoms related to the CCF regressed after treatment and did not recur in the follow-up. Two patients presented residual filling of the CCF at the end of the procedure. The angiographic follow-up revealed in 6 patients of 7 a good patency of the ICA; in 1 patient, there was an ICA asymptomatic occlusion. One patient required transvenous coil occlusion of the cavernous sinus. CONCLUSION: When standard treatments fail, covered stent grafts can be used as a valid alternative in the treatment of CCFs, but more data are needed, especially in the long-term follow-up.